PELAKSANAAN PROGRAM KAMPUS MENGAJAR SEBAGAI RUANG KONTRIBUSI MAHASISWA DALAM PENDIDIKAN DASAR DI SDN 5 POHIJO PONOROGO - Rusmi .; Anisa Dwiki Gusrinda (Universitas Panji Sakti, 2022)
AbstractStudents are agents of change in improving Human Resources by contributing and innovating together to help society. The Independent Learning-Independent Campus Program known as MBKM is a program that provides space for students to develop themselves and contribute, especially in educational matters. In relation to the existing problems, the purpose of writing this article was to examine the realization of the Teaching Campus program as a space for student contributions to basic education at SD Negeri 5 Pohijo. This research applied a qualitative approach with descriptive methods. In data collection techniques, the authors used documentation techniques. The results of this study indicated that the Teaching Campus program has provided a space for students to contribute as a realization of the meaning of agents of change thus the Teaching Campus activities can have a positive impact on all elements involved, particularly around the school environment.Keywords: Teaching Campus, Student Contribution, Elementary School